Aplicação de métodos de alta ordem de precisão na investigação numérica do escoamento em bocais supersônicos - Langhinoti, Pablo Manolo Zych (2017)
The analysis of supersonic flow is important because it is related to high technology equipment and its knowledge can benefit the country. The computational analysis of fluid dynamics allows the study of the physical phenomena involved through the resolution of equations by a numerical method. This work performs and analyses numerical simulations for internal high speed flows in geometries related to rocket engines. It is highlighted the expected behavior of the fluid, through the analysis of the proprieties of the flow as Mach number, pressure and density. The source code used (HYNE2D), has implemented the discretization method through finite volume, the domain is given by unstructured meshes and the advance in time is given by the Runge-Kutta method. For the cases simulated numerically it was considered an isoentropic flow and the fluid as a thermal and calorically-perfect gas.